2019
DOI: 10.3389/fnins.2019.00014
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From Bone Mesenchymal Stem Cells Ameliorate Early Inflammatory Responses Following Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a leading cause of mortality and disability worldwide. Although treatment guidelines have been developed, no best treatment option or medicine for this condition exists. Recently, mesenchymal stem cells (MSCs)-derived exosomes have shown lots of promise for the treatment of brain disorders, with some results highlighting the neuroprotective effects through neurogenesis and angiogenesis after TBI. However, studies focusing on the role of exosomes in the early stages of neuroinfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
135
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(141 citation statements)
references
References 46 publications
5
135
0
1
Order By: Relevance
“…Xin et al reported that miR-17-92 cluster-enriched exosomes could activate the PI3K/Akt/mTOR/GSK-3β signaling pathway and enhance neural plasticity and functional recovery in rodents with stroke [58]. Several authors [59][60][61][62] have also reported the impact of mesenchymal stem cell (MSC) exosomes on functional outcomes (e.g., cognitive and sensorimotor functions) in rodents with traumatic brain injury (TBI). MSC exosomes administered into rodent models of TBI revealed reduced cortical lesions, attenuated cellular apoptosis, and modulated neuroinflammation [59,60].…”
Section: Exosomes In Neuroprotectionmentioning
confidence: 99%
“…Xin et al reported that miR-17-92 cluster-enriched exosomes could activate the PI3K/Akt/mTOR/GSK-3β signaling pathway and enhance neural plasticity and functional recovery in rodents with stroke [58]. Several authors [59][60][61][62] have also reported the impact of mesenchymal stem cell (MSC) exosomes on functional outcomes (e.g., cognitive and sensorimotor functions) in rodents with traumatic brain injury (TBI). MSC exosomes administered into rodent models of TBI revealed reduced cortical lesions, attenuated cellular apoptosis, and modulated neuroinflammation [59,60].…”
Section: Exosomes In Neuroprotectionmentioning
confidence: 99%
“…Exosomes derived from human bone marrow MSCs have also been reported to attenuate neurological injury and promote functional recovery in the swine model of combined TBI and hemorrhagic shock . Furthermore, treatment of controlled cortical impact‐induced TBI mice with bone marrow MSC exosomes reduced the lesion size and promote neurobehavioral performance . In their study, exosomes inhibit neuroinflammation by modulating the polarization of microglia/macrophages.…”
Section: Msc‐derived Extracellular Vesicles For Tbimentioning
confidence: 99%
“…83 Furthermore, treatment of controlled cortical impact-induced TBI mice with bone marrow MSC exosomes reduced the lesion size and promote neurobehavioral performance. 84 In their study, exosomes inhibit neuroinflammation by modulating the polarization of microglia/macrophages. The observed effect was mediated through downregulation of inducible nitric oxide synthase and increase expression of clusters of differentiation 206 and arginase-1.…”
Section: Msc-derived Extracellular Vesicles For Tbimentioning
confidence: 99%
See 2 more Smart Citations